Correlation of bioactive marker compounds of an orally applied Morus alba root bark extract with toxicity and efficacy in BALB/c mice - Langeder, Julia; Koch, Mirijam; Schmietendorf, Hannes; Tahir, Ammar; Grienke, Ulrike; Rollinger, Judith M.; Schmidtke, Michaela (Frontiers in Pharmacology, 2023)
Introduction: In traditional Chinese medicine, the root bark of Morus alba L. is used to treat respiratory infections. Recently, anti-inflammatory and multiple anti-infective activities (against influenza viruses, corona virus 2, S. aureus, and S. pneumoniae) were shown in vitro for a standardized root bark extract from M. alba (MA60). Sanggenons C and D were identified as major active constituents of MA60. The aim of the present preclinical study was to evaluate, whether these findings are transferable to an in vivo setting. Methods: MA60 was orally administered to female BALB/c mice to determine 1) the maximum tolerated dose (MTD) in an acute toxicity study and 2) its anti-influenza virus and anti-inflammatory effects in an efficacy study. A further aim was to evaluate whether there is a correlation between the obtained results and the amount of sanggenons C and D in serum and tissues. For the quantitation of the marker compounds sanggenons C and D in serum and tissue samples an UPLC-ESI-MS method was developed and validated. Results: In our study setting, the MTD was reached at 100 mg/kg. In the efficacy study, the treatment effects were moderate. Dose-dependent quantities of sanggenon C in serum and sanggenon D in liver samples were detected. Only very low concentrations of sanggenons C and D were determined in lung samples and none of these compounds was found in spleen samples. There was no compound accumulation when MA60 was administered repeatedly. Discussion: The herein determined low serum concentration after oral application once daily encourages the use of an alternative application route like intravenous, inhalation or intranasal administration and/or multiple dosing in further trials. The established method for the quantitation of the marker sanggenon compounds in tissue samples serves as a basis to determine pharmacokinetic parameters such as their bioavailability in future studies.